The mechanisms of melanogenesis inhibition by glabridin: molecular docking, PKA/MITF and MAPK/MITF pathways - Chunxing Pan; Xiaoying Liu; Yating Zheng; Zejun Zhang; Yongliang Li; Biao Che; Guangrong Liu; Lanyue Zhang; Changzhi Dong; Haji Akber Aisa; Zhiyun Du; Zhengqiang Yuan (Food Science and Human Wellness)
Glabridin is the main ingredient of hydrophobic fraction in licorice extract and has been shown to have anti-melanogenesis activity in skins. However, the underlying mechanism(s) remain not completely understood. The aim of this study is thus to elucidate the possible mechanisms related to the melanogenesis suppression by glabridin in cultured B16 murine melanoma cells and in UVA radiation induced hyperpigmentation model of BALB/c mice as well. Molecular docking simulations revealed that between catalytic core residues and the compound. The treatment by glabridin significantly downregulated both transcriptional and/or protein expression of melanogenesis-related factors including melanocyte stimulating hormone receptor (MC1R), microphthalmia-associated transcription factor (MITF), tyrosinase (TYR), TYR-related protein-1 (TRP-1) and TRP-2 in B16 cells. Both PKA/MITF and MAPK/MITF signaling pathways were found to be involved in the suppression of melanogenesis by glabridin in B16 cells. Also in vivo glabridin therapy significantly reduced hyperpigmentation, epidermal thickening, roughness and inflammation induced by frequent UVA exposure in mice skins, thus beneficial for skin healthcare. These data further look insights into the molecular mechanisms of melanogenesis suppression by glabridin, rationalizing the application of the natural compound for skin healthcare.